Preliminary Interviews; Career Opportunities; General Knowledge; Current Affairs and Who's Who (Lahore Khwaja Book Depot, 1972)
For all types of commission in the Armed Forces of Pakistan, Permanent commission in the Pakistan Air Force., G. D. (Pilots)., Permanent commission inf the Pakistan Navy., Regular & Short Service Commission in the Engineers, Medical, Education, Veterinary and other branches. Equally useful for Central, Provincial and other Allied Services Competitive Examinations.
Keywords: Commission -- Armed Forces of Pakistan -- Competitive Examinations